Conceptualizing Literary History: A Survey of Poetics in Czech Fiction 1860–1910 (Part One) - Charypar, Michal (Bohemistyka, 2023)
The article provides an innovative model of poetics (or isms, styles, etc.) in Czech prose in the latter half of the long 19th century. It gives an overview of seven individualized and mutually distinct poetics, including ideal, analytical, and psychological realisms, Parnassism, naturalism, impressionism, and decadence. The individual poetics do not represent periods, but exist in parallel, allowing confrontations and intersections either within the author's work or in a specific text, as in the model of Czech literature developed by Dalibor Tureček in the past decade. They are always set in the context of European literature and supported by many illustrative examples. The model is not only typological, but also assumes a diachronic perspective, which can be developed in future scholarly work on the history of Czech literature. The aim is to create a system that can potentially be applied not only to Czech fiction, but possibly also to poetry or drama, in other periods and literatures. Part One of the article concentrates on a general overview and on ideal and analytical realisms.